Editorial - Zeta de Pozo, Rosa (2019)
Journalism, media and technology remain united in the innovative and uncertain world of communication. Big Data and data analysis continues to be the area with “greatest growth within Information and Communication Technologies”. Marc Torrent, director of the Center of Excellence in Big Data in Barcelona, registers 53 percent worldwide adoption, and explains that companies that incorporate Big Data and advanced analytics “improve the effectiveness of their decisions, thanks to the ability to understand what their clients want and how to optimize their processes”.